Snowboarding - Morey, Allan (Minneapolis, Minnesota : DiscoverRoo, an imprint of Pop!, 2021)
This high-powered series gives readers a glimpse into the thrilling world of extreme sports. This book introduces readers to the sport of snowboarding including its history, events, and styles. Also, meet the superstars of the sport! Features in clude infographics, connections questions, and QR codes that link to book-specific online resources.
At the terrain park -- History -- Snowboarding today -- Snowboard safety -- Making connections.
"4D Book!"
Includes index.
Keywords: Snowboarding; Sports; Extreme sports; Extreme sports; Snowboarding; Sports